The effectiveness of auditory intellectually repetition learning aided by questions box towards students’ mathematical reasoning ability grade XI SMA 2 Pati - Agoestanto, Arief; Priyanto, Oei Yuda Setiyo; Susilo, Bambang Eko (Department of Mathematics, Universitas Negeri Semarang, 2018)
The objective of this study is to determine does the AIR learning is effective towards students’ mathematical reasoning ability grade XI SMA 2 Pati on the sequence and the series material. The population in this study is all students grade XI SMA 2 Pati Academic Year 2016/2017. The method used in this study is quantitative method. While the data collection includes test methods, questionnaires, and observations. The results showed that: (1) the mathematical reasoning ability of students grade XI SMA 2 Pati who learn with AIR learning model is reaching the mastery learning; (2) the mathematical reasoning ability of students grade XI SMA 2 Pati who learn with AIR learning model aided by Questions Box is reaching the mastery learning; (3) the mathematical reasoning ability of students grade XI SMA 2 Pati who learn with AIR model aided by Questions Box is better than the mathematical reasoning ability of students who learn with AIR learning model and expository learning model; (4) the mathematical reasoning ability of students grade XI SMA 2 Pati who learn with AIR model aided by Questions Box is better than the mathematical reasoning ability of students who learn with AIR learning model and expository learning model for each group, either low, medium or high. Based on the four results of the above research, it can be concluded that the AIR learning aided by Questions Box is effective towards students’ mathematical reasoning ability grade XI SMA 2 Pati on the sequence and series material.